The Impact of an Erasmus Placement in Students' Perception of their Intercultural Communicative Competence. Issue 4 (3rd July 2016) - Durán Martínez, Ramiro; Gutiérrez, Gloria; Beltrán Llavador, Fernando; Martínez Abad, Fernando
Abstract: Pre- and post-questionnaires answered by UK Nottingham Trent University (NTU) and Spain's University of Salamanca (USAL) students on their placement abroad support a comparative analysis of its impact on their intercultural communicative competence, comprising the awareness, attitude, skills and knowledge dimensions. NTU students started their placements with better results in them all. Yet, while both groups completed their stay with a similarly increased awareness, the knowledge and skills of the USAL group matched the results of NTU students and, whereas the scores of the attitude dimension towards the host country of NTU students did not increase significantly, those of USAL students decreased.